Ferrocene‐substituted bis(ethynyl)anthracene compounds as anticancer agents. (16th October 2017) - Singh, Ajeet; Kumari, Pratibha; Raghuvanshi, Abhinav; Mobin, Shaikh M.; Mathur, Pradeep
Abstract : Three compounds (1 –3 ) were synthesized, where ethynylferrocene is substituted at different positions of anthracene and anthraquinone, and their biological properties were investigated. Compounds 1 –3 were characterized using NMR and mass spectroscopies and confirmed by their single‐crystal X‐ray structure. They were also characterized from electronic and photophysical properties. All three crystal structures were optimized using density functional theory calculations. The presence of C–H⋅⋅⋅π interactions in 1 –3 leads to the formation of two‐ and three‐dimensional networks. The bioactivity of 1 –3 was expressed by molecular docking with various cancerous proteins, which participated in progression of cancer. Compound 2 displayed the best interaction with cancer‐related Aurora A protein in terms of both binding energy (−10.61 kcal mol −1 ) as well as inhibition constant (16.74 nM). The molecular docking result also coincides with cytotoxicity on cancer cell lines (A375, HeLa) and DNA/protein binding affinity. Abstract : The bioactivity of ethynylferrocene‐based compound 2 led to the best interaction with cancer‐related Aurora A protein in terms of both binding energy (−10.61 kcal mol −1 ) as well as inhibition constant (16.74 nM). The molecular docking result further coincides with cytotoxicity for cancer cell lines and DNA/protein binding affinity.